SENSOR FIBER OPTIK BF4R SEBAGAI PENDETEKSI WARNA PADA ALAT PENSORTIR BOBBIN BENANG BERBASIS PLC OMRON CP1E-N 30 DRA DAN SCADA - Fasila, Akbar Tandu; Winarno, Heru (Gema Teknologi, 2015)
Akbar Tandu Fasila, Heru Winarno, in this paper explain that in the modern era, the progress of technology is very important in their daily lives, particularly in the industrial sector. Changes to automated manual system is very developed in order to achieve the maximum point of production and reduce the level of error that often occur in manual systems. It also affects the yarn spinning industry yanl, g now utilize the tools pensortir menerapkkan yarn bobbins with pneumatic system, PLC and SCADA. Planning tool making this sort can not be separated from the fiber optic sensor for identifying the color on each bobbin thread through the intensity of light that is captured by a fiber optic sensor tersbut. The workings of the system works and consists of two cylinders Pneumatic that serves as the actuator, two sensors fiber optics for detecting the light intensity on the bobbin thread, one unit PLC OMRON CP1E-N 30 DRA as the main controller systems, and SCADA as the monitoring system works. Keywords: Bobbin Thread, PLC, SCADA, Fiber Optic Sensor.